KATEGORI DAN FUNGSI TINDAK ILOKUSI DALAM FILM THE DEVIL WEARS PRADA KARYA DAVID FRANKEL (Suatu Analisis Pragmatik) - SUMURUNG, JULIO. B. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT   Language is one of the most important characteristics of human behavior. In communication, people not only utter sentences but also transfer it into behavior and this is called speech act. According to Searle (1970:105), illocutionary act is divided into five categories; those are assertive, directive, commissive, expressive and declaratives. The purposes of this research are to identity, classify, and analyze the category of illocutionary and theory functions through utterances found in the film by The  Devil  Wears  Prada  by David Frankel. The collected data have been taken through the utterances that uttered by the characters and analyzed them descriptively based on the theory of Searle. The  research finding, it shows that there are five categories of illocutionary acts in that film. Those are assertive, directive, commissives, expressive and declarative. The functions of the category of illocutionary act found are asserting, complaining, requesting, begging, offering, thinking, and blooming, congratulations. This study is expected to give contribution to the language development in linguistic studies especially in analyzing illocutionary act through pragmatic analysis. Keywords : Illocutionary Act; Category and Functions, Film;, Pragmatic Analysis